Inhibition of tissue damage by the arachidonate lipoxygenase inhibitor BW755C. - Higgs, G A (1984)
The effects of three anti-inflammatory drugs, which interfere with arachidonic acid transformation by three different enzymes, have been compared by using a simple model of tissue damage and foreign body rejection. In groups of control rats, subcutaneously implanted polyester sponges were rejected after a mean of 12 days. Indomethacin, which selectively inhibits prostaglandin synthesis, did not significantly change time to rejection but BW755C (3-amino-1-[m-(trifluoromethyl) phenyl]-2-pyrazoline), which is a dual inhibitor of prostaglandin and leukotriene synthesis, prolonged time to rejection to a mean of 22 days. The anti-inflammatory steroid dexamethasone, which reduces arachidonic acid metabolism by stimulating the formation of a phospholipase inhibitor, prolonged time to sponge rejection as BW755C did. Treatment with BW755C or dexamethasone was also accompanied by a reduction in total leukocyte numbers in inflammatory exudates collected at 1-14 days, whereas indomethacin increased leukocyte migration on days 1 and 2 and had no effect at later times. These results suggest that the inhibition of the leukotriene-forming lipoxygenase suppresses leukocyte activation and that this leads to a reduced rate of tissue damage in experimental inflammation.